Design of Potent Telomerase Inhibitors using Ligand-based Approaches and Molecular Dynamics Simulations Studies - Bajaj, Shalini; Murahari, Manikanta; Chandra, Mayur Yergeri (Current Drug Discovery Technologies, 2025)
IntroductionTelomerase is a well-recognised and a promising target for cancer therapy. In this study, we selected ligand-based approaches to design telomerase inhibitors for the development of potent anticancer agents for future cancer therapy.MethodsTo investigate the chemical characteristics required for telomerase inhibitory activity, a ligand-based pharmacophore model of oxadiazole derivatives reported from the available literature was generated using the Schrodinger phase tool. This selected pharmacophore hypothesis is validated by screening a dataset of reported oxadiazole derivatives. The pharmacophore model was selected for virtual screening using ZINCPharmer against the ZINC database. The ZINC database molecules with pharmacophore features similar to the selected pharmacophore model and good fitness score were taken for molecular docking studies. With the pkCSM and SwissADME tools we predicted the pharmacokinetic and toxicity of top ten ZINC database compounds based on docking score, binding interactions and identified two in-silico potential compounds with good absorption, distribution, metabolism, and less toxicity. Then both the hit molecules were exposed to molecular dynamic simulation integrated with MM-PBSA binding free energy calculations using GROMACS tools.ResultsThe generated pharmacophore model displayed five features, two hydrophobic and three aromatic rings. The MM-PBSA calculations exhibited that the free binding energy of selected protein-ligand complexes were found stable and stabilized with non-polar and van-der walls free energies.ConclusionOur study suggests that ZINC82107047 and ZINC8839196 can be used as hit molecules for future biological screening and for discovery of safe and potent drugs as telomerase inhibitors for cancer therapy.
Keywords: pharmacophore